Protein Delivery into Plant Cells: Toward In vivo Structural Biology - Cedeño, Cesyen; Pauwels, Kris; Tompa, Peter (Frontiers in Plant Science, 2017)
Understanding the biologically relevant structural and functional behavior of proteins inside living plant cells is only possible through the combination of structural biology and cell biology. The state-of-the-art structural biology techniques are typically applied to molecules that are isolated from their native context. Although most experimental conditions can be easily controlled while dealing with an isolated, purified protein, a serious shortcoming of such in vitro work is that we cannot mimic the extremely complex intracellular environment in which the protein exists and functions. Therefore, it is highly desirable to investigate proteins in their natural habitat, i.e. within live cells. This is the major ambition of in-cell NMR, which aims to approach structure-function relationship under true in vivo conditions following delivery of labelled proteins into cells under physiological conditions. With a multidisciplinary approach that includes recombinant protein production, confocal fluorescence microscopy, nuclear magnetic resonance spectroscopy and different intracellular protein delivery strategies, we explore the possibility to develop in-cell NMR studies in living plant cells. While we provide a comprehensive framework to set-up in-cell NMR, we identified the efficient intracellular introduction of isotope-labeled proteins as the major bottleneck. Based on experiments with the paradigmatic intrinsically disordered proteins Early Response to Dehydration protein 10 and 14, we also established the subcellular localization of ERD14 under abiotic stress.